Węgrzy jako "pars aliqua gentis Massagetum" : ślady późnoantycznej i wczesnośredniowiecznej uczoności w dziele Tomasza archidiakona Splitu. Część 1. Postrzeganie Węgrów we wczesnym średniowieczu z perspektywy zastosowanych w źródłach określeń - Spychała, Lesław (Instytut Historyczny Uniwersytetu Wrocławskiego, 2020)
The article deals with the issue of an isolated view in the medieval historiography of the Latincultural circle, the identification of Magyars as Massagetae. Operating within the established practice of theirage, the litterati tried to determine the role played by emerging ethnic groups by applying methods based onprinciples of etymology and analogy. Thus they identified names of those ethnic units with the ethnonyms known to them from the Bible and ancient literature. In dealing with emerging ethnic units, earlier unknown, they followed the principle of the variability of names of the attested ethnic units. This principle was applied to Hungarians credited with emerging from Scythia and referred to in medieval sources as a gens ignota / exter(n)a.The identification of Hungarians with earlier known ethnic units was strengthened by terms used to describethem as barbari, pagani, infideles.